Growth And Characterization Of AlGaN Thin Films Via Sol-gel Spin Coating Method - Isa, Nurul Atikah Mohd; Sha, Shiong Ng; Hassan, Zainuriah (2016)
In this study, the growth and characterization of aluminum gallium nitride (AlGaN) thin film grown on AlN/Si(Ill) template via sol-gel spin coating method were reported. The structural, morphological and optical properties of AlGaN thin film were compared with GaN thin film which prepared using the same method. The structural and morphological properties of the deposited films were characterized using X-ray diffi·action (XRD), field -emission scanning electron microscope (FESEM) and atomic force microscopy (AFM). XRD results revealed that all the deposited GaN and AlGaN thin films have wurtzite structure and with preferred growth orientation of (002). The FESEM and AFM revealed that the deposited GaN and AlGaN thin films have uniform and smooth surface. However, the AIGaN thin film exhibits more packed grain as compared to GaN. The optical characteristics of the GaN and A!GaN thin films were excessed by using Fourier transform infrared (FTIR) spectrometer. It was observed from the FTIR results that the E1(TO) peak was shifted to higher wavenumber for the AlGaN sample.